Student Management In Online Learning (Case study at SD Inpres 5/81Unra Kecamatan Awangpone Kabupaten Bone) - Muh. Abid Maulana; Rahmawati Patta; Abd. Kadir; Makmur Nurdin (International Journal of Elementary School Teacher, 2022)
The current COVID-19 pandemic has not only brought changes to society, but also education, one of which is the management of students in learning. Student management is an activity, or all efforts and regulatory actions taken by educators or teachers to students in the teaching and learning process. Student management is the teacher's effort in managing the learning process to create effective learning, especially during a pandemic, learning is carried out online. This research is descriptive qualitative research that aims to describe how the description of the implementation of student management in online learning at SD Inpres 5/81 Unra, Kecamatan Awangpone, Kabupaten Bone. The data collection instrument used an open questionnaire and interview guidelines. Data analysis techniques in research are 1) data reduction, 2) data modeling and 3) drawing conclusions. The results of this study indicate that in learning from SD Inpres 5/81 Unra the teacher has implemented student management in online learning effectively. Based on the results of the research and discussion, it can be concluded that the management of students in online learning at SD Inpres 5/81 Unra includes time management, student management and learning management. In learning during the pandemic, it directs teachers in learning by providing learning videos according to the material provided through the WhatsApp application. The teacher also prepares worksheets for students to work on. In addition, supervision of online learning is carried out online through the WhatsApp application and direct visits to students' homes with parental assistance. The assessment carried out in online learning is by asking students to come to school to collect assignments or by sending assignments on the WhatsApp application. The school for now online learning is good enough for students.